An overview of the material science and knowledge of nanomedicine, bioscaffolds, and tissue engineering for tendon restoration - Liang, Wenqing; Zhou, Chao; Meng, Yanfeng; Fu, Lifeng; Zeng, Bin; Liu, Zunyong; Ming, Wenyi; Long, Hengguo (Frontiers in Bioengineering and Biotechnology, 2023)
Tendon wounds are a worldwide health issue affecting millions of people annually. Due to the characteristics of tendons, their natural restoration is a complicated and lengthy process. With the advancement of bioengineering, biomaterials, and cell biology, a new science, tissue engineering, has developed. In this field, numerous ways have been offered. As increasingly intricate and natural structures resembling tendons are produced, the results are encouraging. This study highlights the nature of the tendon and the standard cures that have thus far been utilized. Then, a comparison is made between the many tendon tissue engineering methodologies proposed to date, concentrating on the ingredients required to gain the structures that enable appropriate tendon renewal: cells, growth factors, scaffolds, and scaffold formation methods. The analysis of all these factors enables a global understanding of the impact of each component employed in tendon restoration, thereby shedding light on potential future approaches involving the creation of novel combinations of materials, cells, designs, and bioactive molecules for the restoration of a functional tendon.